Spinal Injuries in Children - Basu, Saumyajit (Frontiers in Neurology, 2012)
About 5% of spinal injuries occur in children – however the consequences to the society are devastating, all the more so because the cervical spine is more commonly affected. Anatomical differences with adults along with the inherent elasticity of the pediatric spine, makes these injuries a biomechanically separate entity. Hence clinical manifestations are unique, one of which is the Spinal Cord Injury Without Radiological Abnormality. With the advent of high quality MRI and CT scan along with digital X-ray, it is now possible to exactly delineate the anatomical location, geometrical configuration, and the pathological extent of the injury. This has improved the management strategies of these unfortunate children and the role of surgical stabilization in unstable injuries can be more sharply defined. However these patients should be followed up diligently because of the recognized long term complications of spinal deformity and syringomyelia.